Strafrecht und Medien - Murmann, Uwe (Universitätsverlag Göttingen, 2016)
Criminal trials often attract great public interest. This interest, again, is essential to criminal justice as such, for in democratic states under the rule of law criminal law and its application need to be asserted and accepted within the public discourse. However, most people do not follow criminal trials as spectators in the courtroom, but by means of public media, such as newspapers, television and - increasingly - the internet. Thus, media outlets gain influence on the public opinion and are able to paint the picture of criminal trials according to their own perception. The media tends to overdraw criminal cases rather than to report the unbiased facts. This leads to tensions between possibly diverging interests of the public, of the judiciary and of the media. This volume addresses these tensions from the perspectives of academics and practitioners, who discussed this issue during an interdisciplinary conference held at the Institute for Criminal Law at the Georg-August-University Göttingen.